Introduction to nuclear and particle physics - Das, Ashok (World Scientific, 2013)
The original edition of Introduction to Nuclear and ParticlePhysics was used with great success for single-semester courses onnuclear and particle physics offered by American and Canadianuniversities at the undergraduate level. It was also translated intoGerman, and used overseas.